Hybrid optical delay and polarization controller - Ahmad Farid Firdaus Yahya (School of Microelectronic Engineering, University Malaysia Perlis, 2011)
The Hybrid Optical Delay and Polarization Controller is a device that combined optical delay and polarization controller. Optical delay is a device to control the optical delay in the fiber and polarization controller is an equipment to control polarization in the fiber. The project is in a small box purposely to save more space where to put this tool and easy to carry anywhere. Two controllers circuit are used to be controlled manually or automatically. For manual control, push button switch is used on the outside of the box and employed ATMEL technology as a controller circuit. For automatic control, a computer program in the computer and PIC technology are used as a controller circuit. This project saves space and five times cheaper than the market price.